Signalling mechanisms underlying doxorubicin and Nox2 NADPH oxidase‐induced cardiomyopathy: involvement of mitofusin‐2. (22nd April 2017) - McLaughlin, Declan; Zhao, Youyou; O'Neill, Karla M; Edgar, Kevin S; Dunne, Philip D; Kearney, Anna M; Grieve, David J; McDermott, Barbara J
Abstract: Background and Purpose: The anthracycline doxorubicin (DOX), although successful as a first‐line cancer treatment, induces cardiotoxicity linked with increased production of myocardial ROS, with Nox2 NADPH oxidase‐derived superoxide reported to play a key role. The aim of this study was to identify novel mechanisms underlying development of cardiac remodelling/dysfunction further to DOX‐stimulated Nox2 activation. Experimental Approach: Nox2 −/− and wild‐type (WT) littermate mice were administered DOX (12 mg·kg −1 over 3 weeks) prior to study at 4 weeks. Detailed mechanisms were investigated in murine HL‐1 cardiomyocytes, employing a robust model of oxidative stress, gene silencing and pharmacological tools. Key Results: DOX‐induced cardiac dysfunction, cardiomyocyte remodelling, superoxide production and apoptosis in WT mice were attenuated in Nox2 −/− mice. Transcriptional analysis of left ventricular tissue identified 152 differentially regulated genes (using adjusted P < 0.1) in DOX‐treated Nox2 −/− versus WT mice, and network analysis highlighted 'Cell death and survival' as the biological function most significant to the dataset. The mitochondrial membrane protein, mitofusin‐2 (Mfn2), appeared as a strong candidate, with increased expression (1.5‐fold), confirmed by qPCR (1.3‐fold), matching clear published evidence of promotion of cardiomyocyte cell death. In HL‐1 cardiomyocytes, targeted siRNA knockdown of Nox2 decreased Mfn2 protein expression, but not vice versa . While inhibition of Nox2 activity along with DOX treatment attenuated its apoptotic and cytotoxic effects, reduced apoptosis after Mfn2 silencing reflected a sustained cytotoxic response and reduced cell viability. Conclusions and Implications: DOX‐induced and Nox2‐mediated up‐regulation of Mfn2, rather than contributing to cardiomyocyte dysfunction through apoptotic pathways, appears to promote a protective mechanism. Linked Articles: This article is part of a themed section on New Insights into Cardiotoxicity Caused by Chemotherapeutic Agents. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.21/issuetoc